STUDENTS' PERCEPTION OF THE FLIPPED MODEL BLENDED LEARNING IN EFL CLASSROOM - Atikah wati; Ajeng Bella Septi Fauzi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
The educational sector in the post-pandemic era, due to the COVID-19 crisis, forces teachers to adapt to new methodologies and instructions in teaching students in EFL classrooms. One of the learning methods used is the flipped model of blended learning. This study aims to determine how the students perceive the learning experience after using the flipped blended learning model in EFL classrooms at the Vocational High School level. That focuses on investigating the students' perception of flipped model blended learning in terms of motivation, Effectiveness, and Engagement. This study used Qualitative research with a case study design. Ten items of a close-ended questionnaire were used as the instrument. The data was then calculated using the Likert Scale. The findings show that students at Losarang Vocational High School had a positive view of motivation, Effectiveness, and Engagement. Specifically, the result of students' perceptions of motivation was 3,11, Effectiveness was 3,31, and EngagementEngagement was 3,27. The students agreed that the flipped model of blended learning improves their learning process. When the students spent more time learning using flipped blended learning, they became more engaged since they had the flexibility to arrange their studies as they see best, wherever and whenever. Students received the flipped model of blended learning in EFL classrooms positively.